KEDUDUKAN SERTIPIKAT HAK MILIK ATAS TANAH YANG TERDAFTAR ATAS NAMA SEORANG AHLI WARIS (Putusan Mahkamah Syar’iyah Nomor : 0220/Pdt.G/2015/MS-Tkn) - ABZA KARANESA (PREMISE LAW JURNAL, 2017)
ABSTRACT Generally, in the division of inheritance will be settled by deliberation, but if a dispute arises between an heir of the other heirs, then the division of inheritance is will be resolved through the courts As for problems raised in this research is the First: "How the power of a certificate as a proof of land rights registered in the name of an heir, Second: How judge the legal considerations in the decision of religion syar'iah No: 0220 / Pdt.G / 2015 / MS-TKN has fulfilled justice for heirs, Third: How legal remedies on the settlement of inheritance and the presence of one of the heir that inhibit the implementation of the division of inheritance. The Research Methods used were normative juridical. The research result revealed that the position of a certificate as evidence of proof of ownership of land registered in the name of an heir, would have the force of law when there is no denial of the other heirs. With the denial of the certificate, the legal force is becoming weaker. The legal considerations of judges in the Court's Syar'iyah decision has fulfilled justice to heirs based on consideration of the judge and the evidence submitted by the parties, turns out it was revealed that the certificate is based on legally flawed right base. Moreover proved the land on which the cases object is still the Rights of together for the certificate to be canceled. The legal solutions on the settlement of inheritance with one of the heirs that inhibit the implementation of inheritance is pursued through deliberation by all the heirs, if not obtained a settlement, can be through mediation requested assistance from the village and subdistrict heads, if still not obtained the agreement, then the inheritance dispute resolution is pursued through the courts. Keywords: Certificates, Property Rights on the Land, Inheritance of Islam